Strategi Pemberdayaan Usaha Mikro dan Kecil melalui Pelatihan dan Kemitraan (Studi pada Industri Meubel di Sulawesi Selatan) - Zainuddin Rahman (Jurusan Manajemen Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2012)
The objective of this research is to discover and understand whether the preparation of resources by the government in the from of skill training and partnership has been successful in empowering Microand small enterprises’The approach used in this research is qualitative one, which is based on phenomenology and puts emphasis on emic perspective (subject) and etic perspective ( researcher, theoryand other related information). The unit of analysis is the individual and situation..Data was collected through observation, in depth interview was conducted and documented. The main instrument in this research is the researcher.The result of improvement of resource through training and protection of micro small and mediun enterprises through business partnership, has not been able to empower micro small and medium entetprises..The inability to the govermment to empower the micro and small enterprises for furniture industry in South Sulawesi through its partiality was caused by the incongruence between the existing formal agencies with the condition of local micro small and medium enterprises, the lack of capacity in the local training agencies.Keywords: Strategy, Empower, Training, Partnership Micro and small Enterprises